Efficacy of neuroendoscopic and small-bone-window craniotomy microsurgery for hypertensive cerebral hemorrhage: a meta-analysis of Chinese RCT studies - Zhi, Tianpeng; Wang, Hang; Wei, Xiangyang; Wei, Zhengjun; Sun, Hong-tao (Frontiers in Neurology, 2024)
Objective To compare the clinical efficacy of neuroendoscopy and small-bone-window craniotomy microsurgery in the treatment of supratentorial hypertensive intracerebral hemorrhage. Methods A search was conducted for Chinese randomized controlled trials on neuroendoscopy and small-bone-window craniotomy microsurgery treatment of hypertensive intracerebral hemorrhage published before February 1, 2024, in PubMed, Embase, Web of Science, Cochrane Library, China National Knowledge Infrastructure, Wanfang Data, and China Science and Technology Journal Database. Meta-analysis was performed using Review Manager 5.4 software. Results We included 9 randomized controlled trials, with 391 cases in the neuroendoscopy group and 403 cases in the craniotomy group. The meta-analysis results showed that compared to the small-bone-window craniotomy group, the neuroendoscopy group had a higher rate of hematoma clearance (95% CI [6.65, 18.52], p < 0.00001), less intraoperative bleeding (95% CI [−294.83, −284.75], p < 0.00001), shorter operation time (95% CI [−138.65, −63.04], p < 0.00001), fewer days in the ICU (95% CI [−8.56, −4.04], p < 0.00001), lower rate of postoperative complications (95% CI [0.15, 0.50], p < 0.0001), lower NIHSS score at 3 months postoperatively (95% CI [−6.82, −5.36], p < 0.00001), and higher ADL score (95% CI [16.5, 20.07], p < 0.00001). All comparison results were statistically significant. Conclusion Compared with small-bone-window craniotomy microsurgery, neuroendoscopic surgery for episodic hypertensive cerebral hemorrhage resulted in a higher rate of hematoma clearance, less intraoperative bleeding, shorter operative time, fewer days in the ICU, a lower rate of postoperative complications and a lower 3-month postoperative NIHSS score, and a higher ADL score.